The Contribution of Parental Support as a Determinant of Learning Motivation in Students with Dyslexia - Marzuqo Sahdiana, Nadiya; Laili, Nurfi (Psikostudia : Jurnal Psikologi, 2026)
In Indonesia, approximately 10% of students have dyslexia, but it often goes undetected. Children aged 6–7 years old generally have mastered reading skills, but individuals with dyslexia face different obstacles. Suboptimal stimulation in reading, writing, and arithmetic during childhood can hinder the development of critical thinking in adolescence. This study aims to examine parents' experiences in providing support that plays a role in increasing the learning motivation of students with dyslexia. The method used is qualitative with a case study approach. Data were collected through semi-structured interviews guided by Smet's theory of emotional, appreciative, instrumental, and informational support. The research subjects were two parents who have children with dyslexia at Private Elementary School X in Sidoarjo Regency. Data analysis was conducted using Strauss and Corbin's techniques, including open coding, axial coding, and selective coding, with validity testing through source triangulation. Parental support was proven to foster learning motivation in dyslexic students. Emotional support builds children's self-acceptance and self-confidence, while reward and instrumental support help create positive learning experiences and academic readiness. Informative support enriched the children's learning strategies and understanding of their condition. These efforts contributed to the development of intrinsic motivation and psychological well-being in dyslexic children. These findings emphasize the importance of holistic parental involvement in creating a conducive learning environment for the development of dyslexic children.